Proteomic analysis of the Simkania‐containing vacuole: the central role of retrograde transport. Issue 1 (20th October 2015) - Herweg, Jo‐Ana; Pons, Valérie; Becher, Dörte; Hecker, Michael; Krohne, Georg; Barbier, Julien; Berger, Hilmar; Rudel, Thomas; Mehlitz, Adrian
Summary: S imkania negevensis is an obligate intracellular bacterial pathogen that grows in amoeba or human cells within a membrane‐bound vacuole forming endoplasmic reticulum (ER) contact sites. The membrane of this S imkania ‐containing vacuole (SnCV) is a critical host–pathogen interface whose origin and molecular interactions with cellular organelles remain poorly defined. We performed proteomic analysis of purified ER‐SnCV‐membranes using label free LC‐MS 2 to define the pathogen‐containing organelle composition. Of the 1, 178 proteins of human and 302 proteins of S imkania origin identified by this strategy, 51 host cell proteins were enriched or depleted by infection and 57 proteins were associated with host endosomal transport pathways. Chemical inhibitors that selectively interfere with trafficking at the early endosome‐to‐trans‐Golgi network (TGN) interface (retrograde transport) affected SnCV formation, morphology and lipid transport. Our data demonstrate that S imkania exploits early endosome‐to‐TGN transport for nutrient acquisition and growth. Abstract : Simkania negevensis is closely related to human pathogenic Chlamydiae. We performed proteomic compositional analysis of the Simkania ‐containing vacuole and observed strong association with host intracellular trafficking pathways. Using selective inhibitors of retrograde transport revealed that Simkania growth is strongly dependent on the early endosome‐to‐trans‐Golgi network (TGN) interface (retrograde transport).